Talent identification in sport: A systematic review - Johnston, K.; Wattie, N.; Schorer, J.; Baker, J. (Sports Medicine, 2018)
Talent identification (TID) programs are an integral part of the selection process for elite-level athletes. While many sport organizations utilize TID programs, there does not seem to be a clear set of variables that consistently predict future success. Objective: This review aims to synthesize longitudinal and retrospective studies examining differences between performance variables in highly skilled and less-skilled athletes in elite-level sport. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to identify relevant studies (N = 20). Results: There was a clear overrepresentation of studies that (1) examined physical profiles of athletes (60%); (2) focused on male samples (65%); (3) examined athletes between the ages of 10 and 20 years (60%); and (4) were published between the years 2010 and 2015 (65%). On closer examination, there was a high degree of variability in the factors that were found to discriminate between skilled and less-skilled individuals. Conclusion: Findings from this review highlight how little is known about TID in elite sport and emphasize the need for greater diversity in TID research.